Front Cover: σ‐Aromaticity in a Fully Unsaturated Ring (Chem. Asian J. 23/2018). Issue 23 (19th November 2018) - Wu, Jingjing; Liu, Xin; Hao, Yulei; Chen, Hongjiang; Su, Peifeng; Wu, Wei; Zhu, Jun
Abstract : σ‐Aromaticity dominating in a fully unsaturated ring (the three‐membered ring of methylenecyclopropene and its metallic analog) is reported, revolutionizing the fundamental scope of the concept of σ‐aromaticity, thus opening an avenue to design σ‐aromaticity in other fully unsaturated systems (illustrated by the upper right of a Tai Chi circle), which are traditionally reserved for the domain of π‐aromaticity. More information can be found in the Full Paper by Jun Zhu et al. onpage 3691 in Issue 23, 2018 (DOI:10.1002/asia.201801279 ).